Understanding police use of force : officers, suspects, and reciprocity - Alpert, Geoffrey P.; Dunham, Roger G. (Cambridge studies in criminology (Cambridge University Press), 2004)
This book examines the use of force by police officers. It includes a brief survey of prior research, and then goes on to present important new data and findings. The authors put forward a new conceptual framework, the Authority Maintenance Theory, for examining and assessing police use of force.